UPAYA PENEGAKAN HUKUM TERHADAP BALAP LIAR DITINJAU DARI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA SORONG PROVINSI PAPUA BARAT DAYA - Jelsy T Toumahu; Dian Mega Erianti Renouw; Novalin M Syauta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze the legal provisions governing illegal street racing under Law Number 22 of 2009 on Road Traffic and Transportation, as well as to examine law enforcement efforts against street racing in Sorong City, Southwest Papua Province. The research employs a normative-empirical method, combining library research with field data obtained through interviews with officers of the Sorong City Traffic Police Unit. The findings indicate that illegal street racing constitutes a traffic violation regulated under Articles 297, 115(b), and 311(1) of Law Number 22 of 2009. Law enforcement is carried out through repressive measures (ticketing, vehicle confiscation, and sanctions) and preventive efforts (regular patrols, traffic education, and inter-agency cooperation). However, the enforcement process still faces several challenges, including low public legal awareness, inadequate deterrent sanctions, and limited monitoring facilities. The study concludes that the effectiveness of law enforcement against illegal street racing in Sorong City requires improvement through regulatory enhancement, stronger institutional coordination, and public legal education to promote sustainable road safety and order. Keywords: Law enforcement, Illegal street racing, Traffic law, Law Number 22 of 2009, Sorong City